Training in normobaric hypoxia and its effects on acute mountain sickness after rapid ascent to 4559 m - Schommer, Kai; Wiesegart, Neele Ruth; Menold, Elmar; Haas, Ute; Lahr, Katrin; Buhl, Hermann; Bärtsch, Peter; Dehnert, Christoph (High altitude medicine & biology, 2010)
In a randomized, placebo-controlled, double-blind study, we tested a 4-week program in normobaric hypoxia that is commercially offered for the prevention of acute mountain sickness (AMS).